Pelatihan Sertifikasi Halal pada Pelaku Usaha Mikro dan Kecil - Fajar Julian Azhari; Ahmad Maulidizen; Abdul Rochim; Andri Mulyana; Irwan Aufi; Ade Muhammad Zikril Hakim (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The main problem in the development of the halal ecosystem in Indonesia is the lack of understanding of business actors regarding the importance of halal certification and the process of obtaining it. This study aims to identify business actors' understanding of halal certification and to formulate effective strategies to increase their awareness and compliance. The research method used is a qualitative method with a case study approach and in-depth interviews with business actors who have participated in the Easy Way to Halal Certification for Micro and Small Business Actors. The results of the study showed that after attending the seminar, business actors' understanding increased significantly, especially in terms of the benefits of halal certification for business competitiveness and consumer trust. Business actors were also able to formulate practical steps to take care of halal certification. These findings indicate the importance of ongoing education and intensive mentoring so that business actors can implement halal certification effectively